Atrial Mitral and Tricuspid Regurgitation: Sex Matters. A Call for Action to Unravel the Differences Between Women and Men - Gual-Capllonch, Francisco; Sáenz de Ibarra, José Ignacio; Bayés-Genís, Antoni; Delgado, Victoria (Frontiers in Cardiovascular Medicine, 2022)
Atrial functional regurgitation is caused by atrioventricular annulus dilation, with normal leaflets and ventricular dimensions and function within the normal range. Its occurrence, in both mitral and tricuspid valves, implies a worse prognosis due to the hemodynamic derangement they produce, but also constitutes a marker of greater comorbidity and more advanced disease. Predisposing conditions for these heart valve dysfunctions are mainly atrial fibrillation and heart failure with preserved ejection fraction. However, other factors like female sex also may be involved and influence their incidence, especially for atrial tricuspid regurgitation. In the present review, we analyze sex differences in the reported prevalence of atrial mitral and tricuspid regurgitation, and suggest possible mechanisms involved. Finally, we underline potential therapeutic and preventive strategies to reduce the burden of these heart valve disorders and discuss research gaps.